2007 Canadian Conference on Electrical and Computer Engineering 2007
DOI: 10.1109/ccece.2007.287
|View full text |Cite
|
Sign up to set email alerts
|

Compact Hardware Implementation of the Block Cipher Camellia with Concurrent Error Detection

Abstract: Abstract-A compact hardware implementation of a block cipher is attractive for any low-cost embedded application like smart cards. In this paper, a compact hardware architecture for Camellia is investigated. In this architecture, encryption and key scheduling share the same datapath and a four s-box iterative structure is employed. In the hardware design of cryptographic algorithms, concurrent error detection (CED) techniques have been proposed not only to protect the encryption and decryption process from ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These results should be put in context by considering that a CED scheme based on hardware redundancy would require more that 100% area overhead. Similar studies for AES [5] and Camellia [6] found that compact implementations with CED resulted in 10.9k gates for AES and 26k gates for Camellia. C. Error Detection Capability The basic components of our compact architecture of ICEBERG are the XORs, S-boxes, registers, and multiplexers.…”
Section: Previous Implementationsmentioning
confidence: 66%
“…These results should be put in context by considering that a CED scheme based on hardware redundancy would require more that 100% area overhead. Similar studies for AES [5] and Camellia [6] found that compact implementations with CED resulted in 10.9k gates for AES and 26k gates for Camellia. C. Error Detection Capability The basic components of our compact architecture of ICEBERG are the XORs, S-boxes, registers, and multiplexers.…”
Section: Previous Implementationsmentioning
confidence: 66%
“…Different ASIC implementations of the Camellia algorithm have been reported in [10,[13][14][15][16][17][18][19][20][21][22][23][24]. In [18] compact and highspeed hardware2 architectures for the 128-bit AES and Camellia block ciphers are presented.…”
mentioning
confidence: 99%